2014
DOI: 10.1080/10408398.2011.614702
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizers: Indispensable Substances in Dairy Products of High Rheology

Abstract: The functionality of stabilizers is apparent in many food applications including dairy products. The role of stabilizers like gelatin, pectins, alginates, carboxymethylcellulose, gums, ispghol, sago starch, and chitosan in the development of dairy products of high rheology, like yoghurt, ice cream, and flavored milk, is discussed in this review. Attention is also paid to comprehend on interactions among milk proteins, minerals, and other milk constituents with the reactive sites of stabilizers to get the desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 107 publications
1
28
0
1
Order By: Relevance
“…This has been confirmed by a decrease in syneresis by 93%, at 0.2 g/100g gum addition without affecting either the texture or flavor of yogurt drink (Kök, 2010). In an acidic product like yogurt, guar gum exhibits highly viscous colloidal dispersion that increases viscosity and reduces syneresis (Tasneem et al, 2014). Brennan and Tudorica (2008) also confirmed that guar gum decreased syneresis in yogurt.…”
Section: Guar Gummentioning
confidence: 59%
See 1 more Smart Citation
“…This has been confirmed by a decrease in syneresis by 93%, at 0.2 g/100g gum addition without affecting either the texture or flavor of yogurt drink (Kök, 2010). In an acidic product like yogurt, guar gum exhibits highly viscous colloidal dispersion that increases viscosity and reduces syneresis (Tasneem et al, 2014). Brennan and Tudorica (2008) also confirmed that guar gum decreased syneresis in yogurt.…”
Section: Guar Gummentioning
confidence: 59%
“…Several studies have indicated the importance of hydrocolloids in yogurt quality (Soukoulis et al, 2007;Saha & Bhattacharya, 2010;Akalin et al, 2012;Tasneem et al, 2014); however, a review of the literature revealed lack of detailed information on the factors influencing WHC. Thus, we would like to discuss and summarize several factors that could influence water holding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with high quality indicators for products is achieved by using a variety of stabilizers, emulsifiers, etc. [6,7], which leads to additional costs of production. Such ingredients perform a certain technological function but they do not enrich a product.…”
Section: Study Of Dietary Fiber Properties In Dairy Mixes Containing mentioning
confidence: 99%
“…Pulp from Sweden's forestry industry supports a quarter of EU's total demand in which cellulose is the most important component (Heinsoo 2017). In the food and beverage industry, polysaccharides such as alginate and starch are extensively used as stabilizers and gelling agents (Tasneem et al 2014). In pharmaceuticals, alginate, starch, cellulose and their combinations have been proposed as ideal materials for biocompatible drug carriers (Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%